Trigeneration Based on Biomass - Specific Field Case: Agricultural Residues from Smallholder Farms in Ghana. (August 2016) - Arranz-Piera, Pol; Bellot, Oriol; Gavaldà, Oriol; Kemausuor, Francis; Velo, Enrique
Abstract: Many remote rural communities are ignored in rural electrification plans due to their remoteness or their relatively low demand potential. Many of those communities are rural agricultural villages that cultivate crops whose residue is a potential solid biomass fuel for power generation using appropriate technologies. This research proposes a feasibility study of trigeneration (heat, power and cold) from small farm typologies with enough clustered crop residue in selected communities in Ghana, as well as definition (prototype level) of the best generation technology. A sample of 11 districts in Ghana were surveyed in order to assess the levels of agricultural waste produced in small holder farms and their possible clustering for supplying these wastes to a hypothetical centralized trigeneration plant. The results obtained in terms of plant capacity, biomass waste yields, energy output flows and economic analysis indicate good prospects for the deployment of trigeneration as a solution in rural agricultural areas of Sub-Saharan Africa